Geography, parental investment, and comparative economic Development - Lothar Grall (Philipps-University Marburg, School of Business and Economics, 2016)
This paper suggests differential parental investment as a theoretical link between geographical conditions and comparative economic development, possibly accounting for the reversal of fortune in the process of development with respect to land productivity. The paper develops an evolutionary growth theory that builds on the trade-off between the quantity and quality of offspring. It advances the hypothesis that individuals living in a society characterized by adverse geographical conditions alter the evolutionary optimal allocation of resources from offspring quantity to offspring quality. Higher parental investment in offspring leads to a lower population density but a higher rate of technological progress in the (initially latent) manufacturing sector. Thus, adverse geographical conditions have a negative impact on economic development in the Malthusian epoch but a positive impact on the timing of the Industrial Revolution. The pattern of parental investment captures the very essence of human capital formation in preindustrial times. It is a slow-changing biological or cultural trait and can therefore be seen as a good candidate for a long-term transmission channel of initial geographical conditions on comparative economic development.
Keywords: O11; I12; J13; 330; Comparative Economic Development; Geographical Conditions; Human Evolution; Industrial Revolution; Parental Investment; Reversal of Fortune